2010
DOI: 10.1002/jsfa.4050
|View full text |Cite
|
Sign up to set email alerts
|

Composition and properties of biologically active pectic polysaccharides from leek (Allium porrum)

Abstract: Leek polysaccharides have relatively high galacturonic and glucuronic acid content and are distinguished with high biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…AIR extracted from the cutting waste of leek displays a very high DM (82%). In this context, a similar, but somewhat lower DM (75%) was determined for the alcohol-insoluble substances extracted from fresh leek by Kratchanova, Nikolova, Pavlova, Yanakieva, and Kussovski (2010). Furthermore, a DM between 60 and 70%, which is common for many (fresh) vegetable matrices (Christiaens et al, 2011;Femenia et al, 1998;Sila, Smout, Vu, Van Loey, & Hendrickx, 2005), was observed for the AIR of rejected carrots and the cutting waste of green beans.…”
Section: Degree Of Methyl-esterification Of Pectinsupporting
confidence: 65%
“…AIR extracted from the cutting waste of leek displays a very high DM (82%). In this context, a similar, but somewhat lower DM (75%) was determined for the alcohol-insoluble substances extracted from fresh leek by Kratchanova, Nikolova, Pavlova, Yanakieva, and Kussovski (2010). Furthermore, a DM between 60 and 70%, which is common for many (fresh) vegetable matrices (Christiaens et al, 2011;Femenia et al, 1998;Sila, Smout, Vu, Van Loey, & Hendrickx, 2005), was observed for the AIR of rejected carrots and the cutting waste of green beans.…”
Section: Degree Of Methyl-esterification Of Pectinsupporting
confidence: 65%
“…Moreover, it has high antioxidant capacity [22]. Leek includes bioactive compounds such as flavonoids, polysaccharides and glucosinolates, as well as numerous organosulfur compounds [23]. Onion is characterized by quercetin and quercetin derivatives content in its composition.…”
Section: Introductionmentioning
confidence: 99%
“…The alcohol-insoluble residue was prepared according to the methodology described by Kratchanova. 14,15 The obtained AIR was purifi ed from the chlorophyll according to the procedure reported by Sengkhamparn. 16…”
Section: Substrates and Enzymesmentioning
confidence: 99%